S02.1 The Public Health Need For Diagnostics and the Differing Pathways to Approval and Use Around the World. (13th July 2013) - Deal, C
Abstract : The global impact of STIs is difficult to understand due to the lack of systematic, coordinated, and standardised surveillance of disease prevalence and incidence. A barrier to these efforts is the lack of easy to use, rapid, diagnostic tests in all regions of the world. Regulatory evaluation and approval of diagnostics varies by country. Common to most approval processes is the need for the diagnostic test to be evaluated for the performance characteristics in an appropriate clinical setting. Parameters that need to be understood are the sensitivity and specificity of the test, as well as practical considerations such as stability and ease of use. The degree of clinical validation and the various ways to design the studies are some of the areas that are approached differently by the various regulatory authorities. Understanding of the various regulatory pathways is important to understanding the scientific considerations necessary to map out a product development plan as diagnostic developers embark on product development in this arena.